Directed plant cell-wall accumulation of iron: embedding co-catalyst for efficient biomass conversion. Issue 1 (December 2016) - Lin, Chien-Yuan; Jakes, Joseph; Donohoe, Bryon; Ciesielski, Peter; Yang, Haibing; Gleber, Sophie-Charlotte; Vogt, Stefan; Ding, Shi-You; Peer, Wendy; Murphy, Angus; McCann, Maureen; Himmel, Michael; et al.
Abstract Background Plant lignocellulosic biomass is an abundant, renewable feedstock for the production of biobased fuels and chemicals. Previously, we showed that iron can act as a co-catalyst to improve the deconstruction of lignocellulosic biomass. However, directly adding iron catalysts into biomass prior to pretreatment is diffusion limited, and increases the cost of biorefinery operations. Recently, we developed a new strategy for expressing iron-storage protein ferritin intracellularly to accumulate iron as a catalyst for the downstream deconstruction of lignocellulosic biomass. In this study, we extend this approach by fusing the heterologous ferritin gene with a signal peptide for secretion intoArabidopsis cell walls (referred to here as FerEX). Results The transgenicArabidopsis plants. FerEX. accumulated iron under both normal and iron-fertilized growth conditions; under the latter (iron-fertilized) condition, FerEX transgenic plants showed an increase in plant height and dry weight by 12 and 18 %, respectively, compared with the empty vector control plants. The SDS- and native-PAGE separation of cell-wall protein extracts followed by Western blot analyses confirmed the extracellular expression of ferritin in FerEX plants. Meanwhile, Perls' Prussian blue staining and X-ray fluorescence microscopy (XFM) maps revealed iron depositions in both the secondary and compound middle lamellae cell-wall layers, as well as in some of the corner compound middle lamella in FerEX. Remarkably, their harvested biomasses showed enhanced pretreatability and digestibility, releasing, respectively, 21 % more glucose and 34 % more xylose than the empty vector control plants. These values are significantly higher than those of our recently obtained ferritin intracellularly expressed plants. Conclusions This study demonstrated that extracellular expression of ferritin inArabidopsis can produce plants with increased growth and iron accumulation, and reduced thermal and enzymatic recalcitrance. The results are attributed to the intimate colocation of the iron co-catalyst and the cellulose and hemicellulose within the plant cell-wall region, supporting the genetic modification strategy for incorporating conversion catalysts into energy crops prior to harvesting or processing at the biorefinery.